Synthesis of CNP-SAR405 delivery system for improved therapeutics anticancer activity using A549 human lung cancer cell lines - Bashirah, Ruqayyah A.; Zamri, Nur Balqis; Alitheen, Noorjahan Banu; Ismail, Saila; Masarudin, Mas Jaffri (Springer Science and Business Media Deutschland GmbH, 2025)
Autophagy, a critical homeostatic process, is increasingly implicated in cancer progression and therapy resistance. SAR405 is a potent inhibitor of the autophagy related PIK3C3/VPS34 complex, offering potential as an anticancer agent. This study reports the synthesis, characterization, and biological evaluation of SAR405-loaded chitosan nanoparticles (CNP-SAR405) designed to improve therapeutic delivery and efficacy in A549 human lung carcinoma cells. CNPs were prepared via ionic gelation using chitosan and sodium tripolyphosphate (TPP), yielding stable monodisperse nanoparticles ~ 77.4 nm, PDI ~ 0.2). Upon SAR405 encapsulation, nanoparticle size increased to ~ 110 nm while maintaining uniform distribution. Encapsulation efficiency reached 80% at 200 nM SAR405, confirmed by UV–Vis spectroscopy. Morphological analyses using FESEM and TEM verified spherical nanoparticle structures, while FTIR confirmed successful SAR405 incorporation. FITC-labelling enabled real-time tracking of intracellular uptake, revealing detectable internalization as early as 12 h post-treatment, with fluorescence intensity peaking at 72 h. In vitro cytotoxicity assays demonstrated enhanced anticancer efficacy of CNP-SAR405 compared to free SAR405, CNP-SAR405 achieved similar cytotoxic effects at 69 nM compared to 100 nM for free SAR405 in A549 cells. Furthermore, co-treatment with the autophagy inducer Torin-2 validated that CNP-SAR405 more effectively inhibited autophagosome formation than SAR405 alone, particularly at the 24-h mark. These findings underscore the potential of chitosan nanoparticle-mediated delivery to increase SAR405 bioavailability and anticancer potency while achieving comparable cytotoxic at a lower dose than free SAR405. The CNP-SAR405 formulation represents a promising nanotechnology-driven approach to targeted lung cancer therapy. All experiments were performed in triplicate biological replicates with technical triplicates, and data were analysed using one-way ANOVA followed by Tukey’s multiple comparison post-hoc test (p < 0.05 considered significant).